Analisis Pengaruh Ukuran Perusahaan, ROA dan DAR terhadap Audit Delay (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2016) - Okalesa Okalesa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Development of capital market in Indonesia has an impact on increasing demand for financial statement audit. A delay in financial reporting is indirectly interpreted by investors as a bad signal for the company. This study aims to analyze the factors that affect the audit delay in the consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) observation period is 6 years from 2011 to 2016. This test uses multiple linear regression model. The sample of the research is 27 companies engaged in the industry of goods and consumption. The results showed partially firm size, ROA, and DAR have significant effect on audit delay. Keywords: Company Size, ROA, DAR, and Audit Delay